ICRF plasmas for fusion reactor applications - Lyssoivan, A.; Koch, R.; Van Eester, D.; Van Schoor, M.; Van Wassenhove, G.; Vervier, M.; Weynants, R.; Buermans, J.; Matthys, T.; Esser, H.G.; Marchuk, O.; Neubauer, O.; et al. (Вопросы атомной науки и техники, 2007)
The ICRF plasma production technique is considered as a promising alternative tool for the following applications in the present and next generation superconducting fusion devices: (i) Wall conditioning in the presence of permanent high magnetic field; (ii) Assistance for the tokamak start-up at low inductive electric field (E₀ ~ 0.3 V/m in ITER); (iii) Target dense plasma production (ne ≥ 10¹⁹ m⁻³) in stellarators. The paper presents a review of the ICRF plasma production technique and its applications in the present-day tokamaks and stellarators. The perspective of the alternative technique applications in ITER is analyzed in the frame of 0-D plasma modeling. ВЧ-метод утворення плазми (ICRF) розглядається як перспективний альтернативний інструмент для таких застосувань у сучасних й майбутніх надпровідних термоядерних установках: (i) ВЧ-чистка стінок в присутності постійного сильного магнітного поля; (ii) Aсистування старту токамака у режимі слабого вихрового електричного поля (E₀~ 0.3 В/м в ITERі); (iii) Створення густої вихідної плазми (ne ≥ 10¹⁹ м⁻³) в стелараторах. Зроблено огляд ВЧ-метода створення плазми та його застосування у сучасних токамаках й стелараторах. В рамках моделювання 0-D плазмовим кодом проведено аналіз перспективності використання даного метода в ITERі. ВЧ-метод создания плазмы (ICRF) рассматривается как перспективный альтернативный инструмент для следующих применений в современных и будущих сверхпроводящих термоядерных установках: (i) ВЧ-чистка стенок в присутствии постоянного сильного магнитного поля; (ii) Aссистирование старту токамака в режиме слабого вихревого электрического поля (E₀ ~ 0.3 В/м в ITERе); (iii) Создание плотной исходной плазмы (ne ≥ 10¹⁹ м⁻³) в стеллараторах. Сделан обзор ВЧ-метода создания плазмы и его применений в современных токамаках и стеллараторах. В рамках моделирования 0-D плазменным кодом проведен анализ перспективности использования данного метода в ITERе.